2008
DOI: 10.1021/jp076001w
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of Local Solvent Structure by a Small Dication:  A Theoretical Study on Structural, Vibrational, and Reactive Properties of Beryllium Ion in Water

Abstract: A molecular based understanding of beryllium chemistry in the context of biomolecules is necessary for gaining progress in prevention and treatment of chronic beryllium disease. One aspect that has hindered the theoretical progress has been the lack of a simple classical two-body potential for the aqueous beryllium ion (Be2+) to be used with biomolecular simulations. We provide new parameters for Be2+ that capture the structural and reactive properties of this small dication. Using classical molecular dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…As part of their study of chronic beryllium disease and the role that beryllium-protein binding may play, Snyder and coworkers carried out a molecular dynamics simulation with the CHARMM force field [26]. Surprisingly, a classical MD simulation using Lennard-Jones and Coluombic potential two-body terms only was able to reproduce reasonably the hydration number and Be-O distance [27]. The QMCF method of Rode also gave a short Be-O distance [28].…”
Section: Introductionmentioning
confidence: 99%
“…As part of their study of chronic beryllium disease and the role that beryllium-protein binding may play, Snyder and coworkers carried out a molecular dynamics simulation with the CHARMM force field [26]. Surprisingly, a classical MD simulation using Lennard-Jones and Coluombic potential two-body terms only was able to reproduce reasonably the hydration number and Be-O distance [27]. The QMCF method of Rode also gave a short Be-O distance [28].…”
Section: Introductionmentioning
confidence: 99%
“…In some of these studies it has been suggested that Be acts as a ''tetrahedral proton'' displacing H + from strong hydrogen bonds. [21][22][23][24][25] This implies that strong hydrogen bonds are ideal binding sites for Be. Besides, this new binding mechanism seems to explain how Be migrates through a biological system passing from one protein to another via exchangeable hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important findings is that the complex in which Be is tetracoordinated to the two X ligands and the two imidazole molecules (structure b in Scheme 1) is not the global minimum of the potential energy surface, as might be expected. 49 Hence, although Be has a clear propensity to be tetracoordinated, 21,23,24,50,51 the formation of beryllium bonds may favor arrangements in which the level of coordination is clearly smaller, because of the significant electron density redistribution associated with the formation of beryllium bonds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beryllium has been widely used in industry for manufacturing nuclear components, electronic devices, golf clubs, aircraft brakes, X-ray tubes, high-temperature ceramics, and structural components in satellites and space shuttles. 1 As beryllium is processed from its oxide form in nature, beryllium aerosol particulates are always generated, which would cause documented illnesses of chronic beryllium disease (CBD) in individuals working in and around the beryllium processing site. The primary hazard associated with beryllium processing is the inhalation of beryllium particles.…”
Section: Introductionmentioning
confidence: 99%